The problem of Alzheimer's : how science, culture, and politics turned a rare disease into a crisis and what we can do about it - Karlawish, Jason (St. Martin's Press, 2021)
"Part case studies, part meditation on the past, present and future of the disease, [this book] traces Alzheimer's disease from its discovery and tells the story of the biomedical breakthroughs that may allow it to finally be prevented and treated by medicine. While it is a scathing indictment of our health care system, it is also an argument for how we can live with dementia; the ways patients can reclaim their autonomy and redefine their sense of self, how families can support their loved ones, and the innovative reforms we can make as a society that would give caregivers and patients better quality of life. Rich in science, history, and characters, The Disease of the Century takes us inside cutting edge laboratories, patients' homes, caregivers' support groups, progressive assisted living facilities, and Jason Karlawish's own practice at the Penn Memory Center"--